Smoking Behavior of Adolescent Determining in SMP Negeri 1 Simpang Empat 2018 - Siregar, Mutiah Saleha; Hidayat, Wisnu; Tarigan, Frida Lina (Sari Mutiara Indonesia University Press, 2018)
Background:Indonesia ranks fifth in the highest number of cigarette consuming countries and ranks third in the country with the highest number of smokers in the world. There is an increase in the number of smokers from age group under 15 years and the highest increase is in the age group 10-14 years. Objectives: This study aimed to determine the factors associated with smoking behavior among male students in SMP Negeri 1 Simpang Empat Asahan in 2018.Metode:This research is an analytic survey with cross sectional study design. Number of sample 128 respondents using total sampling. Data analysis was done using univariate analysis, bivariate with chi square test and multivariate with multiple logistic regression. Results: The result of the research showed that there was the correlation of knowledge (p=0.031<α=0.05), attitude(p=0.001<α=0.05), affordability of access (p=0.015<α=0.05), ad exposure (p=0.00<α= 0.05), parents’role (p=0.002<α0.050), peer role (p=0.001<α=0.05), school’s role (p=0.033<α=0.05). The variable which the most dominant correlation was ad exposure (p=0.003;OR=11.806 95% CI 2.345-47.541). Conclusion:It can be concluded that the ad exposure highly influences the development of smoking behavior in adolescents on the grounds they smoke to be more acceptable to people especially peers and to look more manly.